Effect of heart failure pharmacotherapies in patients with heart failure with mildly reduced ejection fraction - Schupp, Tobias; Bertsch, Thomas; Reinhardt, Marielen; Abel, Noah; Schmitt, Alexander; Lau, Felix; Abumayyaleh, Mohammad S. A.; Akın, Muharrem; Weiß, Christel; Weidner, Kathrin; Behnes, Michael; Akın, Ibrahim (European journal of preventive cardiology, 2024)
The study sought to comprehensively investigate the effect of heart failure (HF) pharmacotherapies in patients with HF with mildly reduced ejection fraction (HFmrEF). In the absence of randomized controlled trials, guideline recommendations concerning HF-related therapies in patients with HFmrEF are limited.Consecutive patients hospitalized with HFmrEF were retrospectively included at one institution from 2016 to 2022. The prognostic value of treatment with beta-blockers (BB), angiotensin-converting enzyme inhibitors, receptor blockers, or receptor-neprilysin inhibitor (ACEi/ARB/ARNI), mineralocorticoid receptor antagonists (MRA), and sodium-glucose-linked transport protein 2 inhibitors (SGLT2i) was investigated for all-cause mortality at 30 months (a median follow-up) and HF-related rehospitalization. A total of 2109 patients with HFmrEF were included. Treatment with BB [27.0 vs. 35.0%; hazard ratio (HR) = 0.737; 95% confidence interval (CI) 0.617-0.881; P = 0.001], ACEi/ARB/ARNI (25.9 vs. 37.6%; HR = 0.612; 95% CI 0.517-0.725; P = 0.001), and SGLT2i (11.9 vs. 29.5%; HR = 0.441; 95% CI 0.236-0.824; P = 0.010) was associated with a lower risk of 30-month all-cause mortality, which was still demonstrated after multivariable adjustment and propensity score matching. In contrast, MRA treatment was not associated with long-term prognosis. The risk of HF-related rehospitalization was not affected by HF pharmacotherapies. Finally, the lowest risk of long-term all-cause mortality was observed in patients with combined use of BB, ACEi/ARB/ARNI, and SGLT2i (HR = 0.456; 95% CI 0.227-0.916; P = 0.027).Beta-blockers, ACEi/ARB/ARNI, and SGLT2i were independently associated with a lower risk of all-cause mortality in patients with HFmrEF, specifically when applied as combined ‘HF triple therapy’. Randomized studies are needed to investigate the effect of HF-related pharmacotherapies in patients with HFmrEF.Although heart failure (HF) with mildly reduced ejection fraction (HFmrEF) affects one out of four patients with HF, limited evidence regarding HF pharmacotherapies in these patients is available. The present study investigates the treatment with beta-blockers (BB), angiotensin-converting enzyme inhibitors, receptor blockers, or receptor-neprilysin inhibitor (ACEi/ARB/ARNI), mineralocorticoid receptor antagonists (MRA), and sodium-glucose-linked transport protein 2 inhibitors (SGLT2i) on long-term outcomes using a large registry-based data set of 2109 patients hospitalized with HFmrEF. Treatment with BB, ACEi/ARB/ARNI, and SGLT2i was independently associated with a lower risk of long-term all-cause mortality, even after multivariable adjustment and propensity score matching, specifically when applied in combination. In contrast, MRA treatment was not associated with outcomes in the present study. The present study supports the evidence that patients with HFmrEF may benefit from HF pharmacotherapies similar than patients with HF with reduced ejection fraction.
Online verfügbar: 21. März 2024
Gesehen am 22.07.2024